A cross-cultural comparison of the ethics of business students - Lysonski, Steven (Journal of business ethics, 1991)
The ethical tendencies of university business students from the USA, Denmark, and New Zealand were examined by analyzing their reactions to ethical dilemmas presented in a set of ethical problem situations. These dilemmas dealt with coercion and control, conflict of interest, physical environment, paternalism and personal integrity. Findings indicate that students' reactions tended to be similar regardless of their country. A comparison of these findings to practicing managers indicated that students and practicing managers exhibit a similar degree of sensitivity to ethical dimensions of business decision-making. Implications are drawn for business education and further research.